Effects and optimization of the use of biochar in anaerobic digestion of food wastes. Issue 5 (May 2016) - Cai, Jiao; He, Pinjing; Wang, Ying; Shao, Liming; Lü, Fan
The addition of various amounts of biochar to anaerobic digestion of food wastes at different ratios of inoculum to substrate (ISR) was investigated to evaluate the effect of biochar as a functional additive and to optimize the additive dosage of biochar. The biochar treatments at ISR 2, 1, and 0.8 shortened the lag phase of digestion by −20.0%–10.9%, 43.3%–54.4%, and 36.3%–54.0%, and raised the maximum methane production rate by 100%–275%, 100%–133.3%, and 33.3%–100%, respectively, compared to control without biochar. Biochar also enhanced the degradation rate of dissolved organics and volatile fatty acids. Furthermore, the amount of biochar with best effectiveness at ISR = 2, 1, and 0.8 was 2.5, 0.625, and 0.5 g g −1 -waste, respectively. Therefore, the effectiveness of biochar depended on the additive amount of biochar and at the same time the inoculum amount, implying a complementary role of abiotic biochar to biotic inoculum.